Democratic Backsliding in South Asia: Recent Anecdotes - Pyakurel, Uddhab; Khangchian, Veronica (Bodhi: An Interdisciplinary Journal, 2024)
Democracy is a political system of government that allows all groups, regardless of race, gender, class or sexual orientation, to participate in politics. Despite its limitations, most people have high hopes for democracy even today. However, the debate over whether democracy works in the contemporary but very complex global order is getting political space in academia and society. This paper explores the state of democracy in South Asia bringing some more ground reality, i.e. recent political upheavals in Sri Lanka, Bangladesh, India, Pakistan and Nepal. While doing so, it extensively reviews the scholarly works of ‘third wave of democracy’ published during and around 1990s and ‘third wave of dictatorship’ published after 2019 and examines whether there is any linkage of scholarly publication and the democratisation process